Assessment of educational outcomes of small group discussion versus traditional lecture format among undergraduate medical students - Joshi, Krishna Prakash; Padugupati, Suhasini; Robins, M. (International Journal Of Community Medicine And Public Health, 2018)
Background: In present scenario, medical students are over burdened with high academic load making learning more complicated than simple. In the recent past a lot of importance has been given for active learning by implementing various approaches like tutorials, seminars, small group discussionsetc. Small group discussion enhances student-faculty interaction, improves communication skills and provides a platform to exchange of ideas, which will result in deeper learning and better academic achievements by students. Present study was conducted to find out educational outcomes of SDG. The objectives of study were to assess and compare the educational outcomes of student’s performance by 2 methods of teaching- Didactic lectures versus SGD and to assess student’s perception towards small group discussions in Community Medicine. Methods: Total 140 students of 7th semester participated in educational experimental quasi study. These participants were divided in to two groups on bases of systematic random sampling. Group A (Roll.no. 1 to 70) and Group B (Roll.no. 71 to 140). For conducting effective SDG, students were divided in 7 subgroups (10 students in each group). Demography (for group A) and family planning (for group B after cross over) topics were selected for SGD. Feedback from students were also recorded. Results: The post test scores of SGD, group A (15.6±3.55) were higher in comparison with that of the lecture session of group B (8.81 ± 2.8). After the crossover, the students exposed to SGD, group B (13.85±3.81) scored more than the students exposed to the lecture group, group A (9.08±2.94).perception of feedback on SGD shows that 80% of the students strongly opine that SGD has improved their performance. Conclusions: Result has shown that SGDs had a positive impact on performance of the students, the mean values in post-tests of both groups were statistically significant. Around 80% of student strongly agreed that SGD is comprehensive tool for in-depth learning by teacher-student interaction and 79% felt that SDG is better than didactic lecture. Significant changes in student’s performance and retention capacity were observed.